Efeito sinérgico entre a dexmedetomidina e a ropivacaína 0,75% na anestesia peridural - Salgado, Paula Fialho Saraiva; Sabbag, Amália Tieco; Da Silva, Priscila Costa; Brienze, Sergio Luís Aparecido; Dalto, Helio Pontes; Módolo, Norma Sueli Pinheiro [UNESP]; Braz, José Reinaldo Cerqueira [UNESP]; Nascimento Junior, Paulo do [UNESP] (Elsevier, 2008)
BACKGROUND. This study aimed to evaluate clinical characteristics of epidural anesthesia performed with 0.75% ropivacaine associated with dexmedetomidine. METHODS. Forty patients scheduled for hernia repair or varicose vein surgeries under epidural anesthesia participated in this study. They were assigned to: Control Group (n = 20), 0.75% ropivacaine, 20 ml (150 mg); and Dexmedetomidine Group (n = 20), 0.75% ropivacaine, 20 ml (150 mg), plus dexmedetomidine, 1 μg.kg -1. The following variables were studied: total analgesic block onset time, upper level of analgesia, analgesic and motor block duration time, intensity of motor block, state of consciousness, hemodynamics, postoperative analgesia and incidence of side-effects. RESULTS. Epidural dexmedetomidine did not affect onset time or upper level of anesthesia (p > 0.05) however it prolonged sensory and motor block duration time (p < 0.05) and postoperative analgesia (p < 0.05), and also resulted in a more intense motor block, 1 (p < 0.05). Values of bispectral index were lower in Dexmedetomidine Group (p < 0.05). There was no difference in incidence of hypotension and bradycardia (p > 0.05). Occurrence of side-effects (shivering, vomiting and SpO 2 < 90%) was low and similar between groups (p > 0.05). CONCLUSION. There is clear synergism between epidural dexmedetomidine and ropivacaine, further this drug association does not bring about additional morbidity.
Synergistic effect between dexmedetomidine and 0.75% ropivacaine in epidural anesthesia
Keywords: Analgesics; Anesthetic techniques; Anesthetics; Dexmedetomidine; Epidural block; Ropivacaine; alpha adrenergic receptor stimulating agent; amide; dexmedetomidine; local anesthetic agent; ropivacaine; adolescent; adult; chi square distribution; clinical trial; controlled clinical trial; controlled study; double blind procedure; drug potentiation; epidural anesthesia; female; human; inguinal hernia; leg; male; middle aged; nerve block; nonparametric test; randomized controlled trial; time; Adolescent; Adrenergic alpha-Agonists; Adult; Amides; Anesthesia, Epidural; Anesthetics, Local; Chi-Square Distribution; Double-Blind Method; Drug Synergism; Female; Hernia, Inguinal; Humans; Lower Extremity; Male; Middle Aged; Nerve Block; Statistics, Nonparametric; Time Factors; Young Adult